2003
DOI: 10.3168/jds.s0022-0302(03)73840-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Parameters for Concentrations of Milk Urea Nitrogen

Abstract: The objective of this study was to use field data collected by dairy herd improvement programs to estimate genetic parameters for concentrations of milk urea nitrogen (MUN). Edited data were 36,074 test-day records of MUN and yields of milk, fat, and protein obtained from 6102 cows in Holstein herds in Ontario, Canada. Data were divided into three sets, for the first three lactations. Two analyses were performed on data from each lactation. The first procedure used ANOVA to estimate the significance of the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
88
10
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 18 publications
30
88
10
1
Order By: Relevance
“…Butler et al (1996) reported a MUN of 22.8 mg/dl for nonpregnant cows, 21.3 mg/dl for cows later identified pregnant and overall mean values of 22.3 mg/dl. Other studies reported lower means of around 12 to 13 mg/dl (Wood et al, 2003;Mitchell et al, 2005), although the range was similar to our results (1 to 50 mg/dl). MU concentration is influenced Godden et al, 2001).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Butler et al (1996) reported a MUN of 22.8 mg/dl for nonpregnant cows, 21.3 mg/dl for cows later identified pregnant and overall mean values of 22.3 mg/dl. Other studies reported lower means of around 12 to 13 mg/dl (Wood et al, 2003;Mitchell et al, 2005), although the range was similar to our results (1 to 50 mg/dl). MU concentration is influenced Godden et al, 2001).…”
Section: Resultssupporting
confidence: 91%
“…In all lactations, the concentrations of MUN were slightly elevated at the start of lactation, reaching minimal level in early lactation, and then rising steadily to maximum values at the end of the lactation. Wood et al (2003) reported similar trends in MUN with stage of lactation. Jonker et al (1998) found a decrease of MUN with advancing DIM from around the second month onward, leading to a curve for MUN similar to that for milk yield.…”
Section: Resultsmentioning
confidence: 53%
“…The average MU at calving was close to 285 mg/L; it then decreased to 225 mg/L at approximately 30 to 40 DIM and finally rose slightly until 280 DIM to the same level as the one at calving. A similar trend was observed by Miglior et al (2007) and Wood et al (2003). As discussed by Wood et al (2003), this trend may be due to the physiological changes and the evolution of the metabolic demands of milk production across DIM.…”
Section: Datasupporting
confidence: 60%
“…A similar trend was observed by Miglior et al (2007) and Wood et al (2003). As discussed by Wood et al (2003), this trend may be due to the physiological changes and the evolution of the metabolic demands of milk production across DIM. However Godden et al (2001) and Wattiaux et al (2005) reported that the MU trend across a lactation was similar to the lactation curve.…”
Section: Datasupporting
confidence: 60%
See 1 more Smart Citation